Chronic Plaque Psoriasis - K.M. Luba; D.L. Stulberg (South African Family Practice)
Chronic plaque psoriasis, the most common form of psoriasis, is a papulosquamous disease defined by erythematous plaques with a silvery scale. The diagnosis usually is clinical, but occasionally a biopsy is necessary. Psoriasis affects 0.6 to 4.8 percent of the U.S. population, and about 30 percent of affected patients have a first-degree relative with the disease. Psoriasis is a T-cell-mediated autoimmune disease, but certain medications and infections are well-known risk factors. Management of psoriasis includes education about chronicity, realistic expectations, and use of medication. Steroids and vitamin D derivatives (e.g., calcipotriene) are the mainstays of topical therapy. Topical steroids and calcipotriene together may work better than either agent alone. Patients with psoriasis involving more than 20 percent of their skin or those not responding to topical therapy are candidates for light therapy; traditional systemic therapy; or systemic treatment with immunomodulatory drugs such as alefacept, efalizumab, and etanercept.